USE OF MODERN TECHNOLOGIES IN THE EDUCATION SYSTEM EDUCATION SYSTEM OF UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
The relevance of the topic of the article is due to the fact that the methods of teaching economic disciplines provide an opportunity for the most effective memorization and learning. The article highlights the features and essence of these teaching methods, and characterized their importance and effectiveness in teaching economic disciplines.  The use of active learning methods in economics creates conditions for the disclosure of students' creative potential, stimulating them to generate new ideas, develop non-standard solutions to economic problems and the formation of innovative thinking. This article analyzes active learning methods in economic disciplines.